PENGARUH KERAGAMAN MENU, KUALITAS PRODUK, CITRA MEREK, DAN IKLAN TERHADAP KEPUTUSAN PEMEBELIAN - Muhammad Wahyu Ali; Handoyo Djoko Waluyo; Sari Listyorini (Jurnal Ilmu Administrasi Bisnis, 2013)
In the restaurant business, which is the key to success is the diversity of menu and the quality of products offered. Consumers will compare the suitability of the sacrifices made by the quality of products and the diversity of the menu offered by the restaurant, other attributes inherent in a product such as brand image and advertising needs to be developed to influence customer purchase. This study aims to determine  effect of the diversity of menu, product quality, brand image, and advertising on consumer purchasing decisions McDonald's Java Mall Semarang. Variable diversity of menu influence the purchase decision of 48.6 percent. Variables quality of the product influence purchase decisions at 54.2 percent. Variables of brand image influence purchase decisions for 47.3 percent. Variable advertising influence purchase decisions of  37.2 percent. Variable menu variety, product quality, brand image, and advertising on purchase decisions for 66.4 percent. This means that the increasing diversity of the menu, product quality, brand image, and advertising is expected to increase consumer purchasing decisions.Based on this research, the McDonald’s Java Mall innovation cause diversity menu, improving the ability of officers in the service, consistency in the application of Quality, Service, Cleanliness, and Value and create the image of a good, proper advertising as well as unique and interesting will positively impact to consumer purchasing decisions